Global perspectives on media events in contemporary society - Fox, Andrew (Advances in media, entertainment, and the arts (AMEA) book series., 2016)
This book seeks to re-define the role of the media in relaying information about current events within a modern context, determining what constitutes the proper presentation of a media event's importance given the ubiquity of media consumption.